2 - Développement, Conditions Sociales et Santé de la Population en Afrique Sub-Saharienne 25 - Azétsop, Jacquineau (African Sociological Review, 2022)
Both intuitively and empirically, studies show that the causal link between development and health in African countries is bidirectional or even cyclical. Several studies have proven that economic progress has positive impacts on health, while the negative impacts of poor health on economic performance are empirically verifiable. The thorny issue of poverty coupled with poor governance, whose roots are structural and contextual, is at root of healthcare system failure. Far from having protective effects on public health, the social conditions in which most people grow and live are the source of most health challenges. These conditions increase people’s exposure to environmental hazards and pathogens, determine access to resources that promote well-being and influence people’s ability to overt diseases. Thus, public health promotion cannot be reduced to clinical interventions, but addresses social organization and its important effects on people’s well-being. A biosocial analysis of health challenges is necessary for identifying the logics of disease production in their complexity and for formulating adequate responses in order to foster radical changes, not only in terms of public health policy but also in terms of social policy. Development policies may then serve as the basis for improving living and health conditions if initiatives aimed at the economic progress favor both the growth of wealth and the promotion of civic equality, thus giving an important authority to legal and social arrangements that promote good governance and social participation in state’s affairs.